Análise de um gerador óptico para um Qubit codificado em um oscilador - Policarpo, Samy Clever (2016)
The fault-tolerant quantum computation scheme proposed by Gottesman, Kitaev, and Preskill (GKP) in Phys. Rev. A, 64, 012310 (2001) can be performed using relatively simple linear optical resources and provides a natural protection against arbitrary small errors. On the other hand, preparing the initial GKP states is a difficult task. A few proposals to generate GKP states have been done over the last years. Our objective here is to analyze the performance of a particular GKP generator that uses cat states, linear optical devices, squeezing, and homodyne detection. We use numerical simulations to study the behavior of the fidelity between the generated and the ideal states and show that the proposal in consideration is indeed a promising scheme.